Utilizing Nanomaterials in Microfluidic Devices for Disease Detection and Treatment - Zhibiao Tian; Yatian Fu; Zhiyong Dang; Tao Guo; Wenjuan Li; Jing Zhang (Nanomaterials)
Microfluidic technology has gained widespread application in the field of biomedical research due to its exceptional sensitivity and high specificity. Particularly when combined with nanomaterials, the synergy between the two has significantly advanced fields such as precision medicine, drug delivery, disease detection, and treatment. This article aims to provide an overview of the latest research achievements of microfluidic nanomaterials in disease detection and treatment. It delves into the applications of microfluidic nanomaterials in detecting blood parameters, cardiovascular disease markers, neurological disease markers, and tumor markers. Special emphasis is placed on their roles in disease treatment, including models such as blood vessels, the blood–brain barrier, lung chips, and tumors. The development of microfluidic nanomaterials in emerging medical technologies, particularly in skin interactive devices and medical imaging, is also introduced. Additionally, the challenges and future prospects of microfluidic nanomaterials in current clinical applications are discussed. In summary, microfluidic nanomaterials play an indispensable role in disease detection and treatment. With the continuous advancement of technology, their applications in the medical field will become even more profound and extensive.